PENGOLAHAN LANJUT LIMBAH CAIR KELAPA SAWIT SECARA AEROBIK MENGGUNAKAN EFFECTIVE MICROORGANISM GUNA MENGURANGI NILAI TSS - Irvan; Bambang Trisakti; Michael Vincent; Yohannes Tandean (Talenta Publisher (Universitas Sumatera Utara), 2012)
Palm oil mill effluent (POME) production in Indonesia is estimated around 28.7 million ton/year. Generally, POME treatment is done conventionally by using facultative ponds. Aside from the vast usage of land and operational cost, this system also emits greenhouse gases. Eventhough, POME is a potential raw resource in producing biogas. Previous researches were done with anaerobic process to produce biogas, but the waste produced still haven’t met the standard quality control requirements. The total suspended solid (TSS) contained in the waste produced from the anaerobic process is still around 400 mg/L, which is the reason why aerobic process is still necessary to drop the number of TSS contained by using effective microorganism. From the result, a 10 day HRT aerobic process can reduce the number of TSS to around 200 mg/L.